Using Innovative Technologies for Chemistry Teaching - Vokhidov Shermuhammad Mamadalievich (Genius Journals, 2022)
In this article are held the examples for using innovative technologies, in examining of organic chemistry in technical University. Describes dignity of multimedia support of lectures, electronic educational complex during independent study of students. Also, here had given a description of innovative types of test tasks, which allows for variability of decision. Use of such types tests, not only allows to modular extend of all the sections of organic chemistry, but also contributes to formation of complex understanding of being studied educational disciplines to students.
Keywords: innovation; organic chemistry; technical University; methodology